Membentuk Kembali Masyarakat: Peran Penting Studi Sosiologis di Tengah Globalisasi: Reshaping Societies: The Vital Role of Sociological Studies amid Globalization - Yusuf Yusuf; Wamaungo Juma Abdu (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
The swift and profound societal changes triggered by the unprecedented COVID-19 pandemic have necessitated rapid adaptations in individual behaviors within daily life routines. This study addresses the vital role of sociological studies in reshaping societies amid globalization within the New Normal Era. Employing a sociological lens grounded in Talcott Parsons’ functionalism theory, this study employs a meticulous and rigorous descriptive qualitative research design. This study investigation draws upon an extensive and systematic collection of diverse bibliographic sources, encompassing previous scholarly research that sheds light on behavioral shifts before and after the pandemic, alongside credible information from mainstream media outlets. The intricate dynamics of societal metamorphosis during the New Normal epoch are intricately intertwined with the inherent complexities of the prevailing social system, actively grappling with the diverse and enduring aftermath of the coronavirus. Notably, Parsons’ AGIL framework emerges as pivotal in facilitating the establishment of a fresh and adaptive social equilibrium. The realization of the New Normal paradigm hinges on the ethical evaluation and calibration of precisely defined indicators, fostering seamless collaboration and integration among diverse community constituents. Ultimately, this study underscores sociological studies’ indispensable and central role in deeply understanding, critically analyzing, and effectively reshaping societies amidst the profound and multifaceted challenges posed by globalization and the transformative impacts of the COVID-19 pandemic.